Students’ Perception towards Pre-Reading Strategy at One of Senior High Schools in Konawe Selatan - Pratama, Aditya (AL LUGHAWIYAAT, 2023)
This study attempts to measure students 'perceptions of the use of pre-reading strategies in learning English in the classroom and to investigate students' perceptions of pre-reading strategies which can help in learning English. This study uses data collection methods through student reflection and observation. The research was conducted at one of the senior high schools. Sixteen students participated in this study by filling out student reflection sheets to obtain information regarding their responses to the use of the pre-reading strategy. The results showed that the students' perceptions of the pre-reading strategy showed more good responses than the students who still experienced difficulties in learning using the pre-reading strategy method. The results of this study indicate the use of pre-reading strategy is encouraged as the result shows that students perceive the activity more easily particularly to understand the learning material given.Keywords: Perception; pre-reading strategy; students’ responses